Performance Analysis for BDS Phase-smoothed Pseudorange Differential Positioning. (28th March 2016) - Tang, Weiming; Cui, Jianhui; Hui, Mengtang; Deng, Chenlong
Abstract : The positioning accuracy of the BeiDou Navigation Satellite System (BDS) can reach up to 10 m (95% confidence level) in both horizontal and vertical components. In order to improve the positioning performance for metre-level navigation, BDS pseudorange differential positioning has been proposed. We introduce the basic principles of BDS pseudorange differential positioning. Then based on the traditional Hatch filter, a modified Hatch filter for dual-frequency phase-smoothed pseudorange is introduced. The phase-smoothed pseudorange differential positioning, whose observations are smoothed by the modified Hatch filter using BDS B1 and B3 and Global Positioning System (GPS) L1 and L2 carrier-phase observations, are applied to determine the roving station's position. Three strategies are used for results analysis. The results show that the longer the baseline length is, the poorer positioning accuracy gets, and the positioning accuracy decline rate of the BDS B3 signal is higher than that of the BDS B1 signal, especially for long baselines. The percentages of the position deviations less than 3 m in horizontal component and 5 m in vertical component for BDS signals can reach up to 95 %.